A Blueprint for Teaching Excellence - Ruth Pickford (Edinburgh Napier University in collaboration with Aston University, the Universities of Dundee and Auckland, 2018)
This article outlines an innovative and highly practical model that holistically and synoptically integrates the factors that underpin strategic approaches to developing teaching excellence within a course, an institution or more widely. It combines and articulates the various drivers towards excellence widely discussed currently, from the perspectives of students, institutions and those who teach them. Integral to the model are the elements of progression, satisfaction and graduate outcomes that align fully with current imperatives around teaching excellence. Drawing upon extant elements of Higher Education pedagogy, this article adopts a Boyerian approach to scholarship integrating original research that has been applied in diverse contexts in an innovative way (Boyer, 1990), to provide a route-map or blueprint for the design and delivery of curriculum, teaching and learning environments. The model will be of use to individuals, course directors, learning and teaching directorates, institutional leaders working in higher education.